THE EFFECT OF GROWTH REGULATORS ON THE QUALITY OF TWO-YEAR-OLD APPLE TREES OF ‘ŠAMPION’ AND ‘JONICA’ CULTIVARS - Magdalena Kapłan; Piotr Baryła (Acta Scientiarum Polonorum: Hortorum Cultus, 2006)
Studies were conducted at the Felin Experimental Station of the Agricultural University in Lublin in the years 2001–2003 and their aim was to estimate the effect of preparations Arbolin 036SL and Promalin 3,6 SL in the form of lanolin paste on the quality of two-year-old trees ‘Šampion’ and ‘Jonica’ cvs. grafted on rootstock M.26. It was shown that the greatest influence on the number of lateral shoots, sum of shoot length and their mean length was exerted by the cultivar and atmospheric conditions in a given year. It was observed that in the majority of trees more lateral shoots were formed by the trees after the application of growth regulators as compared to the control. A singular use of preparations stimulating the branching in the form of lanolin paste in the years with unfavourable weather conditions (2003) was not sufficient to obtain satisfactory effect. The genetic features of a cultivar and the weather conditions in the period of young shoots’ growth had a significant effect on the growth of the studied trees. Preparations Arbolin and Promalin in the form of lanolin paste had no significant effect on the diameter of the rootstock trunks.